Real‐time geographic settling of a hybrid zone between the invasive winter moth ( Operophtera brumata L.) and the native Bruce spanworm ( O. bruceata Hulst) - Jeremy C. Andersen; Nathan P. Havill; George H. Boettner; Jennifer L. Chandler; Adalgisa Caccone; Joseph S. Elkinton (Molecular Ecology, 2022)
Hybridization plays an important and underappreciated role in shaping the evolutionary trajectories of species. Following the introduction of a non‐native organism to a novel habitat, hybridization with a native congener may affect the probability of establishment of the introduced species. In most documented cases of hybridization between a native and a non‐native species, a mosaic hybrid zone is formed, with hybridization occurring heterogeneously across the landscape. In contrast, most naturally occurring hybrid zones are clinal in structure. Here, we report on a long‐term microsatellite data set that monitored hybridization between the invasive winter moth, Operophtera brumata (Lepidoptera: Geometridae), and the native Bruce spanworm, O . bruceata , over a 12‐year period. Our results document one of the first examples of the real‐time formation and geographic settling of a clinal hybrid zone. In addition, by comparing one transect in Massachusetts where extreme winter cold temperatures have been hypothesized to restrict the distribution of winter moth, and one in coastal Connecticut, where winter temperatures are moderated by Long Island Sound, we found that the location of the hybrid zone appeared to be independent of environmental variables and maintained under a tension model wherein the stability of the hybrid zone was constrained by population density, reduced hybrid fitness, and low dispersal rates. Documenting the formation of a contemporary clinal hybrid zone may provide important insights into the factors that shaped other well‐established hybrid zones.